Through the magnifying glass: Empathy's differential role in preventing and promoting traditional and cyberbullying. (July 2019) - Graf, Daniel; Yanagida, Takuya; Spiel, Christiane
Abstract: Empathy is considered a common protective factor against traditional and cyberbullying. Existing studies have only considered broad components of empathy, such as affective and cognitive empathy. However, there are still inconclusive results regarding the role of cognitive empathy in (cyber)bullying. Therefore, we examined relationships between not only components but also subcomponents of empathy and traditional and cyberbullying in order to investigate contextual differences (face-to-face, cyberspace) and unravel the blurry picture regarding cognitive empathy. A total of 521 students (37.4% girls; Mage  = 17.83 years; SD = 2.13) answered questionnaires during regular school hours on their traditional and cyberbullying involvement, empathy and covariates (age, gender, social media use, migration background and gaming attitudes). The results for cognitive empathy revealed no differences in its protective function across contexts. However, the strength of the protective association was stronger for traditional than for cyberbullying. In contrast, affective empathy was not related to either form of bullying. Subcomponents of cognitive empathy exhibited positive and negative associations with (cyber)bullying. Considering subcomponents of affective empathy revealed differential relationships with traditional and cyberbullying. The functional and quantitative differences in empathy's relation to bullying across contexts and the results' potential contribution to the development of environment-specific interventions are discussed. Highlights: Facets of empathy are differentially related to cyber- and traditional bullying. Cognitive empathy is more strongly related to traditional than cyberbullying. Perspective taking is positively related to cyber- and traditional bullying. Online simulation is negatively related to cyber- and traditional bullying. Peripheral responsivity is related to cyber- but not to traditional bullying.